Long-Term Outcomes of Tissue versus Mesh Repair for Inguinal Hernia in India: A 45-Year Single-Surgeon, Single-Center Retrospective Analysis - K Reddy, C M; Reddy, K R; Reddy, C J; Kishore, C M; Nazeer, Nabeel (Journal of Neonatal Surgery, 2025)
This study presents a retrospective analysis of surgical interventions performed for inguinal hernia, aiming to elucidate the challenges associated with herniorrhaphy (tissue repair) and compare the overall outcomes with mesh hernioplasty (tension-free repair) in the Indian context. A survey revealed that approximately 80% of inguinal hernia repairs in India are still conducted using tissue approximation techniques, especially in rural and suburban healthcare settings, due to various underlying factors. The analysis evaluates the relative merits and drawbacks of these two surgical approaches, herniorrhaphy and mesh hernioplasty, in the management of inguinal hernias within the Indian healthcare landscape. The findings of this retrospective study provide valuable insights into the selection of appropriate surgical techniques and highlight the potential implications for patient outcomes, particularly in resource-limited settings.